Comparative Analysis of Impact Strength among Various Polymeric Materials for Orthotic Production - Habiba, Rachel (2024)
The authors acknowledge Fundação para a Ciência e a Tecnologia (FCT, I.P.) for its financial support through the CEMMPRE projects UIDB/00285/2020 and LA/P/0112/2020, CDRSP projects UIDB/04044/2020 and UIDP/04044/2020, and UNIDEMI projects UIDB/00667/2020 and UIDP/00667/2020. Publisher Copyright: © 2024 by the authors.